PENERAPAN METODE EXTREME PROGRAMMING PADA PENGEMBANGAN SISTEM INFORMASI EVALUASI HAFALAN AL-QUR’AN - Dian Riskiyana; Dwi Sakethi; Rico Andrian (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
Monitoring refers to the process of gathering and analyzing information that is systematic and continuous related in improving the program. The Al-Qur’an memorization monitoring system that has been running is systematic, but not yet efficient. Recording memorization that uses conventional method requires a great deal of time to recap memorization. This research aimed to develop a system that can act as a medium for recording and monitoring the Al-Qur’an memorization. This research used the Extreme Programming method. This research result is the development of web based the Al-Qur’an memorization monitoring system with unit testing and acceptance testing that suit the needs of users. The Al-Qur’an memorization monitoring system can see memorization recap, record memorization, see memorized surah and see memorization chart. The Al-Qur’an memorization monitoring system can evaluation in the memorized Al-Qur’an.